Novel fabrication of fluorescent silk utilized in biotechnological and medical applications. (November 2015) - Kim, Dong Wook; Lee, Ok Joo; Kim, Seong-Wan; Ki, Chang Seok; Chao, Janet Ren; Yoo, Hyojong; Yoon, Sung-il; Lee, Jeong Eun; Park, Ye Ri; Kweon, HaeYong; Lee, Kwang Gill; Kaplan, David L.; et al.
Abstract: Silk fibroin (SF) is a natural polymer widely used and studied for diverse applications in the biomedical field. Recently, genetically modified silks, particularly fluorescent SF fibers, were reported to have been produced from transgenic silkworms. However, they are currently limited to textile manufacturing. To expand the use of transgenic silkworms for biomedical applications, a solution form of fluorescent SF needed to be developed. Here, we describe a novel method of preparing a fluorescent SF solution and demonstrate long-term fluorescent function up to one year after subcutaneous insertion. We also show that fluorescent SF labeled p53 antibodies clearly identify HeLa cells, indicating the applicability of fluorescent SF to cancer detection and bio-imaging. Furthermore, we demonstrate the intraoperative use of fluorescent SF in an animal model to detect a small esophageal perforation (0.5 mm). This study suggests how fluorescent SF biomaterials can be applied in biotechnology and clinical medicine.